Low power consumption driving technique for FCD based on LC resonance - Zhang, Ziliang; Cui, Weiwei; Zhu, Yuxuan; Chen, Yong (Radiation detection technology and methods, 2024)
Purpose The purpose is to reduce the power consumption of FCD array without changing the performances of the detector substantially. Method The traditional FCD driver circuit adopts push-pull configuration output structure circuit. When the drive circuit outputs high level voltage, it will charge the pixel capacitance of the FCD. Then, at the low output level, the charge on the capacitor will be shorted to ground. This paper utilizes an LC resonance driving technique. When the FCD is drived by low-level voltage, the charge on the pixel capacitor will not be shorted to the ground, instead the charge are transfer and stored on the inductor and will be reused when the FCD is drived by the high-level voltage. Results Based on this principle, we design a new FCD driver circuit. It can effectively reduce the power consumption up to 70%. We also compare the X-ray energy resolution of this new driver circuit to that of normal driver circuit. In normal driver circuit, the energy resolution is 228 eV@8.04 keV and the charge transfer efficiencies is 0.99994, in this new driver circuit, the energy resolution is 256 eV@8.04 keV and the charge transfer efficiencies becomes 0.99985. Conclusion There is no substantial change in energy resolution and it meets our requirements in space application well. In addition, the new driver circuit is stable and easy to implement.